The state of disinformation: foreign networks on Twitter influenced the brazilian electoral debate - Fundação Getulio Vargas. Diretoria de Análise de Políticas Públicas (2020)
A group of 232 profiles has acted in other countries before and has been spreading messages involving Bolsonaro, Lula and fake news about pedophilia. Among the most influent profiles are Russian media outlets such as RT and Sputnik, the accounts of political leaders from the US and Italy and an American alt-right youtuber. A second network of automated profiles coming from Venezuela, Argentina, Cuba and Ecuador published content supporting the PT candidacy. These two networks we identified indicate external attempts to influence the electoral debate in Brazil by actors of the right and left wings in other countries.